2016
DOI: 10.1002/sim.7009
|View full text |Cite
|
Sign up to set email alerts
|

Discovering early diabetic neuropathy from epidermal nerve fiber patterns

Abstract: Epidermal nerve fibre (ENF) density and morphology are used to study small fibre involvement in diabetic, HIV, chemotherapy induced and other neuropathies. ENF density and summed length of ENFs per epidermal surface area are reduced, and ENFs may appear more clustered within the epidermis in subjects with small fibre neuropathy than in healthy subjects. Therefore, it is important to understand the spatial structure of ENFs. In this paper, we compare the ENF patterns between healthy subjects and subjects suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 22 publications
(59 reference statements)
4
43
0
1
Order By: Relevance
“…Moreover, comparing class 1, with a majority of the diabetic subjects, and class 2, with mainly healthy subjects with relatively low nerve counts, the nonterminal segments in class 2 seem longer. This is in accordance with the finding that the end points tend to be closer to the entry points in the diabetic subjects than in the healthy ones, since more branching points and longer segments before termination would lead to longer distances between the entry and terminal points. Finally, we give an interpretation of what the results would mean for the nerve patterns as a whole in the different classes.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, comparing class 1, with a majority of the diabetic subjects, and class 2, with mainly healthy subjects with relatively low nerve counts, the nonterminal segments in class 2 seem longer. This is in accordance with the finding that the end points tend to be closer to the entry points in the diabetic subjects than in the healthy ones, since more branching points and longer segments before termination would lead to longer distances between the entry and terminal points. Finally, we give an interpretation of what the results would mean for the nerve patterns as a whole in the different classes.…”
Section: Conclusion and Discussionsupporting
confidence: 91%
“…In both papers, the methods used are based on spatial summary statistics, which summarize the spatial structure of the nerves in an image, but do not describe individual nerve fibers. Finally, we recently analyzed data from the feet of the subjects studied in Myllymäki et al We compared the mild and healthy groups both by using spatial summary statistics and by investigating the structure of entry points and the structure of end points within a nerve (see Andersson et al) . Our main findings were that the entry point patterns tend to be more clustered and the end points closer to their entry point in the mild group than in the healthy group.…”
Section: Introductionmentioning
confidence: 95%
“…NCS are normal in patients with primarily smallfibre neuropathy, and these patients typically also have an almost normal clinical examination 140 . The gold stand ard for the diagnosis of smallfibre neuropathy is meas urement of intraepidermal nerve fibre density (IENFD) by skin punch biopsy 141,142 , but this invasive approach is rarely necessary in routine diagnosis and is primarily used for research purposes. Other confirmatory tests of small nerve fibre damage that are most commonly used for research purposes include quantitative sen sory thermal thresholds for reduced cooling detection thresholds or elevated heat thresholds 143 , laser Doppler flare imaging studies 144 and corneal confocal micro scopy to measure nerve fibre length in Bowman's layer of the cornea, which is reduced in diabetic neuropathy 145 .…”
Section: Diagnosis Screening and Prevention Diagnosismentioning
confidence: 99%
“…By using non‐parametric summary statistics it was shown that the nerve fibre patterns of subjects suffering from moderate or severe diabetic neuropathy are significantly more clustered than healthy patterns Waller et al 3 . Using data from feet and a similar non‐parametric analysis, Andersson et al 4 . reported that the spatial pattern of ENFs of subjects with mild diabetic neuropathy is more clustered than healthy patterns.…”
Section: Introductionmentioning
confidence: 99%
“…As Andersson et al., 4 we in this paper focus on comparing healthy subjects and subjects suffering from mild diabetic neuropathy based on the data taken from feet. In the earlier papers, the base points and end point are regarded as realizations from (unmarked) point processes.…”
Section: Introductionmentioning
confidence: 99%